Implementation of POSW in the Packaging Process at PT. SOS to Minimize Waste Defects with the Lean Manufacturing Method 4M1E - Nurrohman, Ade Syahrian; Najmurijal, Muhammad Fikri; Pramuja, Irgi Sugeng; Maulana, Firman Ajib; Virgy, Bunga Azalia; Prastyo, Yudi (Review: Journal of Multidisciplinary in Social Sciences, 2024)
This research aims to improve product quality in the packing process by optimizing the use of POSW kaizen in the finishing stage of the packing process. The main focus of this research is to identify the main causes of frequent flow out of NG products and find effective solutions to improve work methods and maximize checking of goods before the packing stage. The methods used include analyzing the production process, minimizing the defect rate, and implementing evaluation-based continuous improvement. The results showed that it is possible to check each machine conveyor regularly by applying POSW history problems that have occurred and can reduce the level of NG goods entering the pallet. Thus, this research makes a real contribution in improving production efficiency and final product quality in the packaging process.